Mathematics Literacy and Storytelling - Kusumastuti, Fitri Anisa; Priatna, Bambang Avip (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
One of the skills needed to thrive in the fourth industrial revolution is complex problem-solving. This skill is closely related to mathematical literacy. Mathematics literacy defined as the ability of an individual to formulate, use and interpret mathematics in various contexts. This skill was one of the important skills in improving Indonesia PISA’s (Program for International Student Assessment) rank which was still low so we need a learning approach that can give effect to students' mathematics literacy. Through studying the literature, researchers found that storytelling had an effective influence on students' mathematics literacy skills